Weight status and perceived body size in children. Issue 12 (30th August 2009) - Saxton, J; Hill, C; Chadwick, P; Wardle, J
Abstract : Objective: To investigate associations between weight status and body size perception in children in the UK. Design: Cross-sectional survey. Setting: School-based sample in the UK. Participants: 399 children (205 boys, 194 girls) aged 7–9 years. Main outcome measures: Perceived body size was assessed using a visual method (Children's Body Image Scale, matching to images representing body mass indexes (BMI) from 3rd to 97th percentiles) and verbal descriptors from "too thin„ to "too fat„. BMI (converted to BMI SD scores using UK data) was assessed and demographic information was recorded. Results: Modest associations between actual and perceived body size were found with visual (r = 0.43, p<0.001) and verbal (r = 0.41, p<0.001) methods, but there was a consistent response bias towards underestimation. Using visual matching, most children (45%) underestimated their body size, with significantly greater underestimation (p<0.001) at higher BMI. A gender-by-weight group interaction (p = 0.001) showed that at lower weights girls were more accurate than boys, but at higher weights girls were less accurate. Using the verbal scale, the majority of children reported their body size as "just right" in all weight groups (52–73%), with no sex differences. Conclusions: Children can estimate their body size using visual or verbal methods with some accuracy, but show greater underestimation at higher weights, especially in girls. These findings suggest that underestimation is more widespread than has been assumed, which has implications for health education among school-aged children.